Presenting a qualitative model of the use of social media influencers in the behavior of consumers in the luxury cosmetics industry - Seyyed Aref Asgharzadeh; mehdi Rouholamini; Shiba Masoumi; Azadeh Kiapour (ارزش آفرینی در مدیریت کسب و کار, 2023)
The purpose of this research is to present a qualitative model of the use of social media influencers in the behavior of consumers in the luxury cosmetics industry. According to its purpose, the research method is practical, and in terms of implementation, it is qualitative, based on the foundation's data method. The statistical population of the research includes 15 managers of advertising companies with at least 5 years of work experience, managers of online stores in social media and university professors in the field of marketing management who had research. The sample size was conducted with the logic of theoretical sampling and judgmental method and through semi-structured interviews of experts in the field of advertising, and the interviews continued until reaching theoretical saturation. A semi-structured interview was used to collect information. MAXQDA software was used to code the data. The results showed that social media marketing had a total of 11 factors and 93 components extracted and identified. Identified factors include: causal conditions (changes in the way of marketing, technological changes, people's biological changes), central phenomenon (the process of using social media influencers), background and background factors (characteristics of social media influencers, brands), intervening factor (government factors, social insight from social media), strategic factor (using different marketing strategies, measuring influencers' advertising success), consequence (advertising effectiveness). Extended Abstract Introduction Recently, social media channels that have visual content, simple search and quick response have become increasingly popular (Masuda et al, 2022). The amount of time people spend on social media channels has also increased significantly (Arora et al, 2019). The reduction of advertisements in traditional media has led to the growth of social media strategies such as marketing with influential people (Bhaumik & Meng, 2022). In fact, the goal of marketing through influential people is to find a suitable person who can be a good ambassador for introducing the brand and his audience will become potential customers of the respective brand (Kim & Kim, 2022). Influential marketing is a type of marketing in which direct communication is not established with the audience and messages are not sent directly to the audience (Zedan & Salem, 2016). Instead, companies choose the key people of the audience community and convey their messages to the audience through them (Zhang & Huang, 2022). Marketing through influential people can also market diverse products and services, which affects the credibility gained over time (Farivar & Wang, 2022). Luxury goods are part of a new social protocol in which one's identity and self-esteem are determined by visible brands (Cho et al, 2022). Luxury is defined as the highest level of authentic brands including several physical and psychological values. The fundamental motives for acquiring luxury brands are related to interpersonal aspects as well as hedonic factors (Wiedmann, Hennigs & Siebels, 2009). Competition in luxury brands is increasing day by day in the current market (Botonaki et al, 2016). In this competitive scene, luxury brands must understand the attitudes and values ​​of their customers in order to survive, because customers are looking for values ​​beyond ordinary products when consuming luxury goods (Lou et al, 2022). Based on this, the current research is looking for an answer to this question: What is the qualitative pattern of using social media influencers in the behavior of consumers in the luxury cosmetics industry? Theoretical framework Social media These days, when we talk about social media on the Internet, we are actually talking about a virtual and intangible type of human communication network (Nekmahmud et al, 2022). Social media has attracted billions of active users and accumulated masses of users that are increasing exponentially (Gutierrez et al, 2023). Online social media sites usually include a set of user accounts where registered members can post information that they want to share with others (Khodayari et al, 2021). Users are generally involved with two concepts of creating new content or content created by others (Chegini, 2021). Advertising through influencers Today, based on the attraction marketing methodology, what is important for marketing managers is to convert the visitor into a customer, then into a loyal customer, and finally into a promoter (Sajadi et al, 2015). To achieve this goal, various techniques are used, of which marketing through influential people or influencer marketing is one of them (Shekarchi & Valikhani, 2021). In fact, influence marketing is a branch of marketing that focuses on the potential of influential and famous people to direct the brand message to a larger market (Chan et al, 2023). Ren et al, (2023) investigated the effectiveness of endorsement by different social media influencers: the moderating effect of brand competence and warmth. The researchers' findings show that endorsements from influencers who take on an entertaining role attract more engagement (in terms of views, likes, and comments) than endorsements from influencers who are informative. Yeik et al, (2022) have conducted a study under the title of effective social media marketing: the moderating role of materialism. The results show that the trustworthiness and expertise of social media influencers are important predictors for the purchase intention of followers. Furthermore, the moderating effect of materialism on the relationship between attractiveness and purchase intention is significant. It is noteworthy that the effect of attractiveness on purchase intention is greater when materialism is high.